2011
DOI: 10.1039/c0ce00599a
|View full text |Cite
|
Sign up to set email alerts
|

Observations regarding the crystal structures of non-halogenated phenoxyboronsubphthalocyanines having para substituents on the phenoxy group

Abstract: We report the synthesis and systematic description of a series of five para-substituted phenoxy-BsubPcs including their characterization in the crystal state. The nature of the substituents on the phenoxy molecular fragment was chosen so as to vary both the size and electronegativity: specifically with increasingly bulky para-alkyl groups from hydrogen to tert-octyl and a single electronegative substitute (F). Examination of the arrangement of the phenoxy-BsubPcs within single crystals allows us to place each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
86
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 40 publications
(92 citation statements)
references
References 25 publications
6
86
0
Order By: Relevance
“…Each structure shows the same close packed pairs of molecules (dimers), which we have previously noted as a common packing motif for phenoxylated BsubPcs, including phenoxyBsubPc and 4-methylphenoxy-BsubPc. 28 According to the metrics we have previously established 28 a direct quantitative comparison of this packing structure shows that the spacing of the molecules in all of the solvent-free crystal structures varies only slightly ( Table 1). The molecules making up the close packed pairs are the same distance apart (as indicated by the B−B d 1 and C g to C g distances) in each arrangement, with the boron−boron (d 1 ) distance between the closest molecules in different pairs ranging between 5.576(3) Å and 7.011(4) Å for phenoxy-BsubPc and compound 2a, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Each structure shows the same close packed pairs of molecules (dimers), which we have previously noted as a common packing motif for phenoxylated BsubPcs, including phenoxyBsubPc and 4-methylphenoxy-BsubPc. 28 According to the metrics we have previously established 28 a direct quantitative comparison of this packing structure shows that the spacing of the molecules in all of the solvent-free crystal structures varies only slightly ( Table 1). The molecules making up the close packed pairs are the same distance apart (as indicated by the B−B d 1 and C g to C g distances) in each arrangement, with the boron−boron (d 1 ) distance between the closest molecules in different pairs ranging between 5.576(3) Å and 7.011(4) Å for phenoxy-BsubPc and compound 2a, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…4 BsubPcs are known to be aromatic, non-planar, and cone-shaped molecules. [5][6][7][8] Despite being rst synthesized and characterized in the early 1970s, the majority of the synthesis and application work on BsubPcs has been carried out within the last 10 to 15 years. [9][10][11][12] Halo-BsubPcs are relatively easy to prepare by the reaction of phthalonitrile (an ortho-dinitrile) with a boron trihalide templating agent such as BCl 3 (ref.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Recently,a no verall efficiency of 4.69 %h as been achieved by using BsubPc chloride (Cl-BsubPc;F igure 1a) as an electron acceptorw hen paired with sexithiophene (a-6T,F igure 1a). [5][6][7][8][9][10][11][12][13][14] For the most part, the derivatives we have synthesized are amenable to vacuum processing and fabricationi nto OPVs by sublimation. [4] Our laboratory has been interested in the synthesis of new BsubPc derivatives for some time now.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Our laboratory has been interested in the synthesis of new BsubPc derivatives for some time now. [5][6][7][8][9][10][11][12][13][14] For the most part, the derivatives we have synthesized are amenable to vacuum processing and fabricationi nto OPVs by sublimation. For ex-ample,w eh ave recently shown that ad erivativeo ther than Cl-BsubPc, pentafluorophenoxy BsubPc( F 5 -BsubPc), can function within ap lanar heterojunction OPV as either an electron-acceptor or electron-donor material.…”
Section: Introductionmentioning
confidence: 99%